Calibration and Development Tests on a Coshocton Type Run off Sampler - madhavan, K. (Journal of Soil and Water Conservation, 2022)
A number of devices provide fairly accu- rate means for developing run off hydrographs of stream flow from the stagedischarge record. But no automatic method for measurement of sediment load corresponding to the runoff hydrograph has yet been developed in a practical form. Civil Engineers have developed only means of obtaining representative samples of bed, bed load and suspended load. The careful analysis of a number of such samples taken over the entire cross section of a stream and the tedious process of their accurate summation will only yield the total load of the stream at the time of sampling. But the sediment load is varying in streams from time to time; and estimating the total sediment transported in a day or month based on the data obtained once will, certainly yield results far from true. Therefore, study of variation in sediment load in different portions of a runoff hydrograph is a dimcult task at present owing to the nonavailability of an automatic method of estimating sediment transport.